The Effectiveness of Using Artificial Intelligence for Media Monitoring in Crisis Prediction: A Survey of Private Sector Companies (The International Journal of Educational Sciences and Arts, 2025)
This study aims to assess the effectiveness of employing artificial intelligence (AI) in media monitoring to predict crises in the private sector. It relies on a survey-based methodology involving 150 media monitoring specialists working in private sector companies. The findings reveal that the workforce in this field predominantly consists of young and middle-aged professionals - age groups expected to respond positively to AI technologies. Most participants held a bachelor’s degree, followed by diploma holders, and finally, PhD holders, indicating a relatively high academic level among professionals in this domain. Media studies emerged as the most common field of specialization, followed by public relations and marketing, reflecting a diversity in professional backgrounds with a notable focus on communication-related disciplines. Over one-third of the companies surveyed were found to be utilizing AI in media monitoring, affirming the growing trend of technological adoption in the sector. Half of the respondents acknowledged that media monitoring significantly contributes to crisis prediction, with a slightly higher percentage recognizing an even greater impact when AI is integrated into the process. Participants demonstrated a strong awareness that speed, accuracy, data volume, and analytical capabilities form a solid foundation for effective AI utilization in crisis-related media monitoring. The results also highlighted that the challenges are not limited to technical aspects but extend to human and managerial factors. This calls for a holistic approach involving conscious leadership, ongoing training, and suitable infrastructure to ensure successful AI implementation. Furthermore, the accuracy and localization of tools, along with continuous human development, are critical components. Finally, the study found that local platforms particularly “Lucidya” are the most widely adopted, while foreign platforms or those less adapted to the Arab context face notable challenges in terms of adoption and usage.
Keywords: Artificial Intelligence; Media Monitoring; Crisis Prediction; Private Sector Companies